ANALISIS PRODUKTIVITAS PADA UD. PUJI MULYA - Andrew Manuhutu; Zainal Arief (LPPM Universitas Bina Bangsa, 2023)
UD. Puji Mulyaâ€ is a trading company engaged in the food sector, namely crackers that do not leave the taste of onions. This business was founded on November 17, 1998 by Mr. Sukandar. Prior to establishing this business, Mr. Sukandar worked in the same field. With his hard work, he founded this business with his wife. UD. Puji Mulya is located in the middle of the city crowd, precisely on Jl Medokan Semampir AWS 2 No 23 Kota Surabaya, East Java. In the beginning, this business was initiated by Mr. Sukandar, who wanted to start a business based on the experience he had gained. Armed with the skills and experience he gained from participating in the same business, he was able and succeeded in attracting market share so he could have employees. Initially, this business only had 3 production employees and 7 resellers. But with the passage of time, this cracker business is growing and has many employees. For the production process itself there are 5 employees, while for resellers as many as 20 people. The Marvin E. Mundel method has a different model from other productivity calculation models, namely the use of index numbers. An index number is a number or figures that can statistically indicate a change or difference in the price of one or several types of certain goods. Basically, an index number is a quantity that shows variations in changes in time or space regarding a particular matter. The use of this method is also to look for calculations of labor productivity, energy costs, other costs, raw material costs, machine costs. Capital, depreciation, fixed costs. For the calculation results can be formulated as follows. Labor Productivity Rp. 969,246, Energy Rp. 627,000, Other Expenses Rp. 1,159,247, Raw Material Rp. 448,600, Capital Rp. 447.198. Machine Rp. 14,336, Depreciation Rp. 9,746, Fixed Costs Rp. 79,109.